Islamic literature: definition, nature and scope - Hassan, Md Mahmudul (IIUC Studies, 2018)
Literature is a pellucid mirror that reflects the reality of life, society and the universe. It emanates from ideas, emotions, and beliefs of individual or collective personality irrespective of national, linguistic, cultural, religious and stylistic differences. Islamic literature deals with the features of all aspects of Islam. It is not confined in person, group or nation as well as place or time, but represents a clear appeal for the whole humanity forever. The paper aims at studying the definition of Islamic literature and then sheds light on identifying the nature and scope of this literature. IIUC Studies Vol.13 December 2016: 43-52